Stylistic Analysis of the Song Kartonyono Medot Janji by Denny Caknan - Lestari, Dewi (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
The lyrics of this song are the lyrics of a dangdut song sung by Denny Caknan in Javanese. The interesting thing to study further is the use of diction and the theme using stylistics, namely by looking at the style of language used. The purpose of this study was to analyze the stylistics contained in the lyrics of the song "Kartonyono Medot Promise" Denny Caknan. The study of stylistics is directed to discuss the content of literary works. In general, regulating stylistic studies includes diction or word choice (lexical choice), sentence structure, figure of speech, partnership, rhyme patterns, and dimensions used for authors or available in literary works. This study aims to analyze the use of diction and themes contained in the lyrics of the song Kartonyono Medot Promise sung by Denny Caknan. The method used is a qualitative descriptive method because the object is the text of the Song Lyrics. The data taken is the lyrics of a song by Denny Caknan entitled Kartuyono Medot Promise. Like the style chosen by the author, stylistic theory is used, that is, it does not see aesthetics in song lyrics. As the end of this method is the result of data analysis presentation. The presentation of the results of the data analysis begins with the presentation of the diction on the data source contained in the lyrics of the song Denny Caknan. Then proceed with an explanation of the theme of the lyrics. The results of the research found are diction and theme in the song Kartonyono medot promises, which was popularized by Denny Caknan. Keywords: song lyrics, stylistic analysis, denny caknan